Serum 25-hydroxyvitamin D3, parathyroid hormone and blood pressure in an elderly cohort from Germany : a cross-sectional study - Jungert, Alexandra; Roth, Heinz; Neuhauser-Berthold, Monika; Justus Liebig University Giessen (My University, 2012)
Background: Although several studies indicate a link between vitamin D status and blood pressure (BP), the results are inconsistent. The purpose of this study is to investigate whether in predominantly non-obese elderly people without vitamin D deficiency or very high intact parathyroid hormone (iPTH) levels serum 25-hydroxyvitamin D3 [25(OH)D3] and iPTH are independently associated with BP.Methods: Cross-sectional data of 132 non-institutionalised subjects (90 women and 42 men, aged 66- 96 years) from Giessen, Germany, were analysed. Serum 25(OH)D3 and iPTH were measured by an electrochemiluminescence immunoassay and BP was determined with a sphygmomanometer. We performed univariate and multiple regression analyses to examine the influence of 25(OH)D3 and iPTH on BP with adjustments for age, body composition and lifestyle factors.Results: While iPTH had no impact on BP, 25(OH)D3 was negatively associated with systolic BP in men, but not in women. After splitting the cohort into antihypertensive medication users and non-users, 25(OH)D3 was a significant predictor for systolic and diastolic BP only in men not receiving antihypertensive medicine, even after multiple adjustment. Adjustment for 25(OH)D3 resulted in an inverse association of iPTH with diastolic BP also only in men without intake of antihypertensive medicine.Conclusions: In elderly men without vitamin D deficiency and not taking antihypertensive medicine, 25(OH)D3 may be a negative determinant of BP, independent of iPTH, body composition and lifestyle factors. Furthermore, iPTH may be an independent negative determinant of diastolic BP in men not taking antihypertensive medicine.
Keywords: vitamin D status; blood pressure; non-obese elderly people; intact parathyroid hormone (iPTH); ddc:610